Detecting Defects in Composites Using Combined Heating/Cooling: Theory and Experiments; Journal of Nondestructive Evaluation; Vol. 43 - Chulkov A. O. Arseniy Olegovich; Vavilov V. P. Vladimir Platonovich; Shagdyrov B. I. Bator Ilyich; Kladov D. Dmitry; Burleigh D. Douglas (2024, 2024)
Title screen